Endometrial recognition of pregnancy occurs in the grey short-tailed opossum (Monodelphis domestica). Issue 1905 (26th June 2019) - Griffith, Oliver W.; Chavan, Arun R.; Pavlicev, Mihaela; Protopapas, Stella; Callahan, Ryan; Maziarz, Jamie; Wagner, Günter P.
Abstract : In human pregnancy, recognition of an embryo within the uterus is essential to support the fetus through gestation. In most marsupials, such as the opossums, pregnancy is shorter than the oestrous cycle and the steroid hormone profile during pregnancy and oestrous cycle are indistinguishable. For these reasons, it was assumed that recognition of pregnancy, as a trait, evolved in the eutherian (placental) stem lineage and independently in wallabies and kangaroos. To investigate whether uterine recognition of pregnancy occurs in species with pregnancy shorter than the oestrous cycle, we examined reproduction in the short-tailed opossum ( Monodelphis domestica ), a marsupial with a plesiomorphic mode of pregnancy. We examined the morphological and gene expression changes in the uterus of females in the non-pregnant oestrous cycle and compared these to pregnancy. We found that the presence of an embryo did not alter some aspects of uterine development but increased glandular activity. Transcriptionally, we saw big differences between the uterus of pregnant and cycling animals. These differences included an upregulation of genes involved in transport, inflammation and metabolic-activity in response to the presence of a fetus. Furthermore, transcriptional differences reflected protein level differences in transporter abundance. Our results suggest that while the uterus exhibits programmed changes after ovulation, its transcriptional landscape during pregnancy responds to the presence of a fetus and upregulates genes that may be essential for fetal support. These results are consistent with endometrial recognition of pregnancy occurring in the opossum. While the effects on maternal physiology appear to differ, recognition of pregnancy has now been observed in eutherian mammals, as well as, Australian and American marsupials.